The Effect of Campus Teaching Program on Increasing Student Civic Engagement - Umami, Lisa; Anggraeni, Leni; Tanshzil, Sri Wahyuni (Jurnal Pendidikan Ilmu Sosial, 2023)
This study aims to determine and analyze the influence of teaching campus programs on increasing civic engagement. This research uses a quantitative approach with a descriptive method. Furthermore, the results obtained were analyzed using a partial t test and simple linear regression. The contribution made by students in the implementation of this teaching campus program is the involvement of citizens (students), it can be known through the summary model of linear regression test results, we can know that the magnitude of the correlation value (R) is equal to 0.708 of the results can be obtained coefficient of determination (R Square) of 0.501 means that in the implementation of campus teaching program contributed 50.1% in increasing student civic engagement. While 49.9% civic engagement can be influenced by other variables that are not studied. Then the hypothesis test results show that the value of tcount = 9.015 ttable 1.989, then it can be concluded that H1 or the first hypothesis is accepted. This means that there is an influence between the implementation of campus teaching programs (X) to increase student civic engagement (Y).